A Literature Review on Fostering Teaching English as Foreign Language (EFL) Using Digital Activities - Alghamdi, Faten Ahmed Saeed; Alnajami, Mai Mohammed Lutfi (Journal of Curriculum and Teaching Methodology, 2023)
Information Communication Technology (ICT) plays a crucial role in society’s daily life, whether in developed or developing nations. Information technology is generally used for everyday entertainment and communications and for improving education and supporting it. Following a systematic literature review, this paper aims to assess students’ language skills developed by applying digital activities in classes of English as Foreign Language (EFL). This review analyzes online activities, perceived usefulness, and foreign language skills by highlighting the challenges and advantages of digital activities in EFL classes. Furthermore, the paper highlights the perceived benefits of these activities and the ability to use various digital applications and devices functions to have more substantial outcomes while teaching and learning English. Finally, the paper also generates implications for the educational systems by identifying the roles of English teachers in promoting learning strategies through the use of technology and improving their abilities in utilizing technology in their classes.